Sex and the Cabaret: Dada’s Dancers - Hemus, Ruth (Nordlit, 2007)
The photograph of Hugo Ball, dressed in cardboard costume and conical hat, reciting the sound poem Karawane at a Cabaret Voltaire soirée, before being carried off stage in quasi-religious paroxysm, has achieved iconic status in the history of Dada. It is a-if not the-quintessential image of Zurich Dada. Ball’s image, reproduced countless times, embodies and mythologizes the Dada cabaret and its innovation of sound poetry. It is scarcely surprising that the photograph is treasured, granting as it does a glimpse into Dada performances that have become infamous but remain irretrievable.